The system of energy efficiency indicators of caldron equipment functioning for heating and hot water boilers - Novoseltsev A.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2006)
Principles of construction of the system of power indicators harmonized with the normative base of European Union are offered. The existent traditional system of parameters of power efficiency of caldron equipment functioning is systematized for heating and hot water supply. The examples of application of the developed indicator system are given.